Neuromuscular treatment approach for women with chronic pelvic pain syndrome improving pelvic pain and functionality. Issue 1 (16th September 2021) - Patil, Soha; Daniel, Gabrielle; Vyas, Rakhi; Tailor, Yogita; Howell, Melanie; Ahmed, Tayyaba; Reutter, Christian; Shrikhande, Allyson
Abstract: Aims: Reporting the effects of treating underlying myofascial dysfunction and neuropathic pain in women with chronic pelvic pain syndrome (CPPS). Methods: Retrospective longitudinal study of 186 women with CPPS treated with ultrasound‐guided peripheral nerve blocks and trigger point injections to pelvic floor muscles alongside pelvic floor physical therapy once weekly for 6 weeks in an outpatient setting. Visual Analogue Scale (VAS) and Functional Pelvic Pain Scale (FPPS) questionnaires quantified pain and function in the pelvis. Working, intercourse, sleeping, walking, running, lifting, bladder, and bowel were the function categories. Statistical significance was established by p value less than .05 in paired two‐sample t ‐test. Results: VAS improved by 2.14 where average VAS before treatment was 6.61 (standard deviation [ SD ] 2.45; p  < .05, 95% confidence interval [CI] = 6.26–6.96) and average VAS after treatment was 4.47 ( SD 2.71; p  < .05, 95% CI = 4.08–4.86). Total FPPS decreased by 3.38 from 11.26 ( SD 6.51; p  < .05, 95% CI = 10.32–12.19) before treatment to 7.88 ( SD 6.22; p  < .05, 95% CI = 6.99–8.78) after treatment. Working, intercourse, and sleeping accounted for the highest statistically significant improvement. Conclusion: Findings support the success of the comprehensive treatment protocol. Patients who had persistent symptoms after a full course of pelvic floor physical therapy experienced improvements in pain levels and function once it was combined with ultrasound‐guided nerve blocks and trigger point injections, interactively treating underlying neuromuscular dysfunction.